2021
DOI: 10.3390/biomedicines9101462
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles Exhibit Favorable Properties to Promote Tissue Integration of Biomaterials

Abstract: Due to the demographic change, medicine faces a growing demand for tissue engineering solutions and implants. Often, satisfying tissue regeneration is difficult to achieve especially when co-morbidities hamper the healing process. As a novel strategy, we propose the incorporation of zinc oxide nanoparticles (ZnO NPs) into biomaterials to improve tissue regeneration. Due to their wide range of biocompatibility and their antibacterial properties, ZnO NPs are already discussed for different medical applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Because ZnO nanostructures may form reactive oxygen species (ROS) and release Zn 2+ ions, they are physiologically active, and toxicological studies always accompany the creation of novel ZnO-based nanomaterial to assess their biocompatibility [ 47 ]. While the use of modest doses of ZnO NStr enhances cell development, differentiation, and proliferation [ 48 ], as well as tissue regeneration, enhancing angiogenesis and osteointegration processes [ 49 ], multiple studies have shown that this is accompanied by ZnO antibacterial and antifungal capabilities [ 50 ]. Furthermore, ZnO NStr exhibits selectivity for specific cell lines, making them prospective candidates for cancer cell killing [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because ZnO nanostructures may form reactive oxygen species (ROS) and release Zn 2+ ions, they are physiologically active, and toxicological studies always accompany the creation of novel ZnO-based nanomaterial to assess their biocompatibility [ 47 ]. While the use of modest doses of ZnO NStr enhances cell development, differentiation, and proliferation [ 48 ], as well as tissue regeneration, enhancing angiogenesis and osteointegration processes [ 49 ], multiple studies have shown that this is accompanied by ZnO antibacterial and antifungal capabilities [ 50 ]. Furthermore, ZnO NStr exhibits selectivity for specific cell lines, making them prospective candidates for cancer cell killing [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also assume along with previous reports that metals in nanoform allow to release the ions gradually over longer period of time that can show more therapeutic efficacy compared to metal salts/ionizable salts. [80,81] Based on the overall exciting results, the comprehensive toxicity profile as well as preclinical assessment of CMnNP in animal model has been initiated which are beyond the range of the current work.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Further analysis included total vessel area, total vessel length, mean vessel thickness and number of branching points. For this purpose, manual counting as well as a specific software was used (v3.0.0, KML Vision GmbH, IKOSA AI Platform, Graz, Austria), as described before [ 46 ]. For immunohistochemical analysis, eggs were processed as following.…”
Section: Methodsmentioning
confidence: 99%
“…The chicken chorioallantoic membrane (CAM) assay is a well-proven and standardly used in-vivo model to monitor angiogenesis [ 42 , 43 , 44 , 45 , 46 ]. Among other preferences, the model has a low cost, simplicity, easy accessibility, and reliability [ 47 ].…”
Section: Introductionmentioning
confidence: 99%